2018
DOI: 10.29359/bjhpa.10.2.01
|View full text |Cite
|
Sign up to set email alerts
|

The effect of n‪icotine on oral health

Abstract: Background: Nicotine absorbed by the skin and also by the digestive, respiratory and excretory systems is one of the most known toxins found in tobacco. This work reviews available literature on the influence of nicotine on human health, and in particular on the oral cavity.Material/Methods: A review of literature related to the topic of the paper. Results:Numerous studies indicate that nicotine adversely affects human health. It exerts a negative effect at the cellular level by modifying metabolism, and distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This issue has been studied extensively. However, studies in the field of mental and general health have proved that they are tied very closely with a relationship with personality traits and environmental psychological factors [ 168 , 169 , 170 , 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…This issue has been studied extensively. However, studies in the field of mental and general health have proved that they are tied very closely with a relationship with personality traits and environmental psychological factors [ 168 , 169 , 170 , 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…leukoplakia, pathologic variations in the mucous membrane or tongue, and tumor. It also decreases salivary pH and increases phosphorus-ion concentration resulting in a significant acidic environment and leading to dryness of the mouth, xerostomia, all the above-mentioned factors increase the accumulation of Candida in the oral cavity,[6] otherwise the subjects included in the study group were healthy.…”
Section: Discussionmentioning
confidence: 99%
“…It also affects microflora of the oral cavity, by increasing the number of destructive bacteria and pathogenic fungi. [6] It mixes with plasma proteins, and attaches to the mucous membrane depending on pH, higher the pH greater the lipophilicity; vigorous resorption by an organic membrane which further causes xerostomia and supports the colonization of Candida . Nicotine also decreases salivary pH by the accumulation of calcium and phosphorus ions, and its addiction is a critical factor in the progress of potentially malignant disorders such as leukoplakia that increases the adherence of Candida fungi in the oral cavity, making lesion more vulnerable to malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…It also has major negative effects on the oral cavity. Evidence suggests that there is an established link between nicotine and oral diseases such as periodontal diseases, candidiasis, precancerous lesions, dry socket, and xerostomia [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dental education institutions worldwide have policies to encourage students to introduce tobacco cessation programs to their patients [ 16 ]. Studies have also reported on the willingness of smokers to quit if their dentists recommend it to them [ 5 ]. Tobacco cessation interventions have shown varying degrees of effectiveness in dental care settings [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%